2013
DOI: 10.1039/c3dt32302a
|View full text |Cite
|
Sign up to set email alerts
|

CFA-2 and CFA-3 (Coordination Framework Augsburg University-2 and -3); novel MOFs assembled from trinuclear Cu(i)/Ag(i) secondary building units and 3,3′,5,5′-tetraphenyl-bipyrazolate ligands

Abstract: The syntheses of H2-phbpz, [Cu2(phbpz)]·2DEF·MeOH (CFA-2) and [Ag2(phbpz)] (CFA-3) (H2-phbpz = 3,3',5,5'-tetraphenyl-1H,1'H-4,4'-bipyrazole) compounds and their crystal structures are described. The Cu(I) containing metal-organic framework CFA-2 crystallizes in the tetragonal crystal system, within space group I4(1)/a (no. 88) and the following unit cell parameters: a = 30.835(14), c = 29.306(7) Å, V = 27 865(19) Å(3). CFA-2 features a flexible 3-D three-connected two-fold interpenetrated porous structure cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…MOFs based on [M 3 (µ‐PZ) 3 ] (M + = Cu + or Ag + ) SBUs were reported. Interestingly, the triangular [Cu 3 (µ‐PZ) 3 ] SBU in the polypyrazolate and Cu(I)‐containing frameworks can be transformed to [Cu 3 (µ 3 ‐OH) (OH) 2 (H 2 O) (µ‐PZ) 3 ] upon oxidation . Xiang and co‐workers have also reported the FJU‐66 based on the triangular [Cu 3 (µ‐PZ) 3 ] cluster and linear bipyrazole ligand .…”
Section: Stable Metal–organic Frameworkmentioning
confidence: 99%
“…MOFs based on [M 3 (µ‐PZ) 3 ] (M + = Cu + or Ag + ) SBUs were reported. Interestingly, the triangular [Cu 3 (µ‐PZ) 3 ] SBU in the polypyrazolate and Cu(I)‐containing frameworks can be transformed to [Cu 3 (µ 3 ‐OH) (OH) 2 (H 2 O) (µ‐PZ) 3 ] upon oxidation . Xiang and co‐workers have also reported the FJU‐66 based on the triangular [Cu 3 (µ‐PZ) 3 ] cluster and linear bipyrazole ligand .…”
Section: Stable Metal–organic Frameworkmentioning
confidence: 99%
“…However, until now, only a few reports have appeared in the literature where Cu-MOFs were successfully applied as oxidation catalysts. 14 Our previous studies on the reactivity of CFA-2 (a Cu(I)-containing MOF) toward molecular oxygen for instance have shown that this compound is stable during oxidation and reduction of the Cu ions, suggesting its usage in liquid-phase oxidation reactions. 13 Some years ago we had started the development of Cu-containing MOF catalysts containing pyrazole ligands for the purpose of introducing oxygen functions into the C-H bonds of organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…14 Our previous studies on the reactivity of CFA-2 (a Cu(I)-containing MOF) toward molecular oxygen for instance have shown that this compound is stable during oxidation and reduction of the Cu ions, suggesting its usage in liquid-phase oxidation reactions. 14,18 Polynuclear metallocyclic coordination units of the type [{Cu II (μ-OH)(μ 2 -pz)} n ], n = 6, 8, 9, 12 and 14, have been described, 19 which might become SBUs of the as yet undiscovered MOFs. Similar to carboxylate-type ligands, pyrazolates are known to form μ 2 -bridges between metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Such breathing effects have been repeatedly reported for different MOF structures. [26][27][28][29] Unfortunately, many attempts to collect a single crystal diffraction pattern of a completely dry single-crystal of CFA-8 were…”
Section: Crystal Structure Analysismentioning
confidence: 99%